2022
DOI: 10.1056/nejmoa2113708
|View full text |Cite
|
Sign up to set email alerts
|

Valoctocogene Roxaparvovec Gene Therapy for Hemophilia A

Abstract: BACKGROUNDValoctocogene roxaparvovec (AAV5-hFVIII-SQ) is an adeno-associated virus 5 (AAV5)-based gene-therapy vector containing a coagulation factor VIII complementary DNA driven by a liver-selective promoter. The efficacy and safety of the therapy were previously evaluated in men with severe hemophilia A in a phase 1-2 dose-escalation study. METHODSWe conducted an open-label, single-group, multicenter, phase 3 study to evaluate the efficacy and safety of valoctocogene roxaparvovec in men with severe hemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
223
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(275 citation statements)
references
References 31 publications
6
223
0
6
Order By: Relevance
“… 13 , 16 In a phase 3 trial, participants who received 6 × 10 13 vg/kg experienced a significant increase from baseline in FVIII activity at 2 years post-infusion, as well as significantly reduced FVIII utilization and bleeding compared with their baseline values while receiving FVIII prophylaxis pre-infusion. 17 , 18…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 16 In a phase 3 trial, participants who received 6 × 10 13 vg/kg experienced a significant increase from baseline in FVIII activity at 2 years post-infusion, as well as significantly reduced FVIII utilization and bleeding compared with their baseline values while receiving FVIII prophylaxis pre-infusion. 17 , 18…”
Section: Introductionmentioning
confidence: 99%
“…AAV vector-mediated gene therapy trials for hemophilia A and B clinical have shown promising results. Some participants have presented meaningful expression of FVIII [51][52][53][54][55][56] or FIX, [57][58][59][60][61][62][63] shifting their phenotype from severe to mild or even achieving normal factor levels after a single vector injection. Table 3 shows the ongoing hemophilia A and B gene therapy clinical trials.…”
Section: Gene Therapy For Hemophiliamentioning
confidence: 99%
“…Despite the encouraging results of the recent hemophilia gene therapy clinical trials, several issues remain unclear and unresolved. The variability in FVIII and FIX expression levels among the clinical trial participants and the unpredictable responses are observed in both hemophilia A 52,53,54,55,64 and B gene therapy trials. 59,60,61,62,63,65,66 Furthermore, the cellular immune response is AAV vector dose dependent, and the ideal immunosuppressive therapy still needs to be determined.…”
Section: Gene Therapy For Hemophiliamentioning
confidence: 99%
“… 4 With the phase 3 data now available, it is clear that this decline seems too optimistic. The FVIII expression after the first year was 43 IU/dL, but 24 IU/dL after 2 years, 2 indicating a decline of 44%.…”
mentioning
confidence: 94%